GLOBAL ALGORITHMS, LOCAL CULTURES: Understanding Children’s Content Legibility on Youtube - Annisah, Tania (UIN Mataram dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2025)
This study investigates the legibility of children’s content on YouTube, examining how it is presented, created, and consumed within the context of participatory parenting and Youtube algorithm. Using Jürgen Habermas' public sphere framework, the research explores how digital platforms like YouTube shape participatory media practices, particularly in producing accessible and developmentally appropriate content for young audiences. The study adopts a purposive sampling method, by selecting videos based on YouTube’s algorithmic recommendations to simulate the user experience and exploring how the algorithm presents what they deemed as children content. Then, YouTube API is used to provide a broader overview of children’s content trends, while visual content analysis examines the visual and narrative elements that contribute to content legibility. Findings reveal that while YouTube serves as a collaborative affinity space for children’s content, promoting informal learning and interaction, its algorithm-driven and commercialized nature often undermines content authenticity and diversity, raising concerns about its alignment with children’s cognitive and developmental needs. The study underscores the importance of enhancing the legibility of children’s content in Youtube’s affordances to ensure it is engaging, educational, and appropriate for its intended audience.